Morphological changes of tissues after using high-frequency electrosurgical devices «ERBE ICC 200» and «EFA» for treatment of combined pathology of anal canal and rectum - Balytskyy, V. V.; Kuryk, O. G.; Zakharash, M. P. (Морфологія / Morphologia / Morfologìâ, 2018)
Background. On the modern stage of society development the quantity of proctological diseases increases considerably and among them the dencity of combined pathology of anal canal and rectum grows rapidly and it is becoming from 35 to 65%. Objective. To study morphological changes in tissues of anal canal and rectum during treatment of their combined pathology with using high – frequency electrosurgical devices “ERBE ICC 200”, “EFA” and usual metal scalpel and also compare them. Methods. The results of treatment of 164 patients with combined pathology of anal canal and rectum with using high – frequency electrosurgical device “ERBE ICC 200”, the results of treatment of 114 patients with using high – frequency electrosurgical device “EFA” and the results of treatment of 112 patients with using usual metal scalpel have been analyzed. Results. During the investigation have been established that using of high – frequency electrosurgical device “ERBE ICC 200” follows the formation of thin layer of coagulation necrosis with depth 0,286±0,15мм аnd using of high – frequency electrosurgical device “EFA” follows the formation of the layer of coagulation necrosis with thickness 0,254±0,18мм. Conclusion. Using of high – frequency electrosurgical devices “ERBE ICC 200” and “EFA” causes the slight intensity of tissues necrosis with formation of thin layer of coagulation necrosis which is from 0,074 to 0,436 мм, determining cosmetic efficasy of the operation.